EXPLORING EFL TEACHERS’ NEW PEDAGOGICAL CONTENT KNOWLEDGE OF GENRE-BASED APPROACH - Suharyadi Suharyadi; Utami Widiati; Yazid Basthomi (University of Kuningan, 2021)
This study aimed at exploring the EFL teachers’ pedagogical content knowledge of GBA and English instruction in the Indonesian context. The data were collected from 42 senior high school English teachers by making use of a set of questionnaires, interviews, and observations. The first type of data was analyzed through a response counting to calculate the scores and percentages, with which the categories of teachers’ knowledge were engineered. Meanwhile, the second type of data was analyzed by describing all indicators in the observation checklists (in the forms of spoken cycle and written cycle and four stages of teaching: building knowledge of the field, modeling of the text, joint construction of the text, and independent construction of the text). The data analysis reveals that the English teachers’ pedagogical content knowledge of GBA can be classified into two major groups: 38.1% English teachers had deep knowledge and 61.9% English teachers had shallow knowledge. In connection to the classroom teaching, teachers with these different levels of knowledge are identical in implementing the guidelines of spoken and written cycles. One of the essential implications is that both categories of EFL teachers need to understand theories of GBA and concepts of GBA used in the curriculum more in-depth as the reference and signpost to perform a better classroom teaching.